DUAL FORM OF HIGHER EDUCATION AS A PRODUCT OF SOCIAL PARTNERSHIP - Perevozova, Iryna Volodymyrivna; Pobihun, Serhii Andriiovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article actualizes the introduction of the dual form of higher education as a product of well-established cooperation of all subjects of social partnership with clearly defined areas of influence and feedback.